MINERALOGY OF THE OVERBURDEN ROCKS OF THE KOKLAN W-MO DEPOSIT (SOUTH URALS) - E.V. Belogub; K.А. Novoselov; E.E. Palenova; P.V. Khvorov (Минералогия)
The Koklan W-Mo deposit is overlapped by Mesozoic-Cenozoic rocks 120–140 m thick, which may be subdivided in four members on the basis of variable proportions of the rock-forming minerals (quartz, hydromica (with glauconite), smectites and X-ray amorphous phase) and the presence of clinoptilolite and calcite. Mineral composition was identified using an X-ray diffractometry. The horizon of oolitic iron ores occurs at the bottom of sedimentary sequence. The consistent composition of members throuth the section indicates stable formation conditions of sedimentary sequence and promising use of overburden rocks during exploitation of the deposit.